Economic losses caused by brinjal shoot and fruit borer, Leucinodes orbonalis Guen (Lep.: Pyralidae) (Indian Journal of Arid Horticulture, 2013)
Brinjal has been a stable vegetable in our diet since ancient  time and being grown in all cropping seasons round the  year. It has several vernacular names viz., egg plant,  aubergine, baingan badone, kausi, vangi, vazhuthana  (Yawalkar, 1985). Brinjal is highly productive and usually  find its place as the poor man's crop. It is rich source of  minerals (calcium, magnesium, phosphorus, sodium,  potassium, chlorine, iron etc.), vitamins and also has some  medicinal importance (Choudhary, 1967). In production  and productivity, India stands second in the world after  China. The total area under cultivation of this crop in our  country is 6.12 lack hectares with an annual production of  105.63 lack tones with a productivity of 17.3 Mt / ha. In  Rajasthan, it is grown in an area of 5560 hectare with an  annual production of 0.22 lack tones with a 3.941 Mt/ ha  productivity (Anonymous, 2010). It is generally grown in  all districts of Rajasthan during summer and rainy seasons.  The brinjal crop is attacked by a number of insect pests right  from germination to harvesting, namely, jassids, Amrasca  biguttula biguttula (Ishida); whitefly, Bemisia tabaci (Genn.); aphid, Aphis gossypii Glover; lace wing bug,  Urentius sentis Distant; Hadda beetal, Henosepilachna  vigintioctopunctata (Fab.), shoot and fruit borer, Leucinodes orbonalis Guen.; and stem borer, Euzophera  perticellaRag.
Keywords: nursery; spraying; orbonalis; Anonymous